Peran Moderasi Corporate Social Responsibility pada Pengaruh Profitabilitas terhadap Nilai Perusahaan - Putra, I Gede Angga Adnyana; Suarmanayasa, I Nengah (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The purpose of this study was to examine the role of corporate social responsibility moderation on the effect of profitability on firm value. This research was a type of quantitative research that was associative and causal. The subjects used in this study were the textile and garment sub-sector companies listed on Indonesia Stock Exchange. While the objects in this study include firm value, profitability and corporate social responsibility. This study used a sample of 16 companies, where the sample was obtained through purposive sampling technique. The data used were collected through document recording techniques, then analyzed using a moderating regression data analysis technique through the test of absolute difference in value. The study was carried out obtained results that (1) significantly, profitability has a positive influence on firm value, and (2) corporate social responsibility plays a role in moderating effect of profitability on firm value.